Ileosigmoid knotting: a rare cause of acute intestinal obstruction in an elderly patient - Kumar, Manish; Kumar, Satendra; Gupta, Sanjeev Kumar; Khanna , Seema; Gupta, Shubham Kumar; Digumarthi Asha Rani; Hoda, Inzamam ul (International Surgery Journal, 2023)
Ileosigmoid knotting (ISK) is difficult to diagnose preoperatively due to its rarity and uncommon presentation. It has a high mortality rate; hence early diagnosis and immediate surgical intervention are required. This report describes a case in an 80-year-old male patient with gangrenous ileal loops and sigmoid colon and was managed with resection of gangrenous bowel loops and double stoma, Patient was discharged with a functional stoma and good well-being and was further followed up.